Agriculture in the City of the Future? (Economic and Political Thought, 2023)
Cities embody the idea of change, being at the same time the impulse and driving force of this change. Urban agriculture is also a part of this process, constituting one of the contemporary perspectives of the urban future. Urban agriculture in its current form of integration is a new functional element of cities gaining increasing importance for the future cities i.e. sustainable, green, resilient and smart cities.
Keywords: city, urban agriculture, innovations